Diversity and Interrelations Among the Constitutive VOC Emission Blends of Four Broad-Leaved Tree Species at Seedling Stage - Fitzky, Anne Charlott; Peron, Arianna; Kaser, Lisa; Karl, Thomas; Graus, Martin; Tholen, Danny; Pesendorfer, Mario; Mahmoud, Maha; Sandén, Hans; Rewald, Boris (Frontiers in Plant Science, 2021)
Volatile organic compounds (VOCs) emitted by plants consist of a broad range of gasses which serve purposes such as protecting against herbivores, communicating with insects and neighboring plants, or increasing the tolerance to environmental stresses. Evidence is accumulating that the composition of VOC blends plays an important role in fulfilling these purposes. Constitutional emissions give insight into species-specific stress tolerance potentials and are an important first step in linking metabolism and function of co-occurring VOCs. Here, we investigate the blend composition and interrelations among co-emitted VOCs in unstressed seedlings of four broad-leaved tree species, Quercus robur, Fagus sylvatica, Betula pendula, and Carpinus betulus. VOCs of Q. robur and F. sylvatica mainly emitted isoprene and monoterpenes, respectively. B. pendula had relatively high sesquiterpene emission; however, it made up only 1.7% of its total emissions while the VOC spectrum was dominated by methanol (∼72%). C. betulus was emitting methanol and monoterpenes in similar amounts compared to other species, casting doubt on its frequent classification as a close-to-zero VOC emitter. Beside these major VOCs, a total of 22 VOCs could be identified, with emission rates and blend compositions varying drastically between species. A principal component analysis among species revealed co-release of multiple compounds. In particular, new links between pathways and catabolites were indicated, e.g., correlated emission rates of methanol, sesquiterpenes (mevalonate pathway), and green leaf volatiles (hexanal, hexenyl acetate, and hexenal; lipoxygenase pathway). Furthermore, acetone emissions correlated with eugenol from the Shikimate pathway, a relationship that has not been described before. Our results thus indicate that certain VOC emissions are highly interrelated, pointing toward the importance to improve our understanding of VOC blends rather than targeting dominant VOCs only.